Doktor Faustus: Das Leben des deutschen Tonsetzers Adrian Leverkühn, erzählt von einem Freunde - Mann, Thomas 1875-1955 (Frankfurt am Main Fischer, 1960)
The novel is a re-shaping of the Faust legend set in the context of the first half of the 20th century and the turmoil of Germany in that period. The story centers on the life and work of the (fictitious) composer Adrian Leverkühn. The narrator is Leverkühn's childhood friend Serenus Zeitblom, who writes in Germany between 1943 and 1946. Leverkühn's extraordinary intellect and creativity as a young man mark him as destined for success, but his ambition is for true greatness. He strikes a Faustian bargain for creative genius: he intentionally contracts syphilis, which deepens his artistic inspiration through madness. He is subsequently visited by a Mephistophelean being (who says, in effect, "that you can only see me because you are mad, does not mean that I do not really exist"), and, renouncing love, bargains his soul in exchange for twenty-four years of genius. His madness—his daemonic inspiration—leads to extraordinary musical creativity.
Paul Thomas Mann (1875-1955) was a German novelist, short story writer, social critic, philanthropist, essayist, and the 1929 Nobel Prize in Literature laureate. His highly symbolic and ironic epic novels and novellas are noted for their insight into the psychology of the artist and the intellectual.
Originally published in 1947
Keywords: Faust; 20th Century (1901-2000); Literature; Novel; Creativity; Germany